Perspectives of Palestinian physicians on the impact of the Gaza War in the West Bank - Husam Dweik; Ahmad Abu Hadwan; Beesan Maraqa; Ameed Taher; Therese Zink (Elsevier, 2024)
Background: The West Bank has been under military occupation since 1967. When the Israeli army attacked Gaza after October 7th, 2023, the situation in the occupied West Bank became much worse. We interviewed Palestinian physicians about practicing under occupation and how the Gaza War has impacted their professional and personal lives. Methods: This qualitative study was conducted from December 2023 to February 2024 and involved 15 individual interviews by reaching out to networks of practicing physicians across the West Bank, purposefully sampling physicians in different geographic locations in hospital and clinic-based practices. The data were analyzed with inductive coding and organized into themes. Results: Violence and the threat of violence affected many elements of life and health. Restricted mobility, financial hardship, educational challenges, and fear about safety and the future affected physical and psychological health, making patients sicker and physicians' jobs harder. Lack of medications and treatments worsened chronic medical conditions. Mental health care was in demand due to acute stress and persistent trauma. Physicians struggle fulfilling their professional commitment to care for patients. They worried about the future and struggled to care for their families. Conclusion: Life under occupation on the West Bank has become harsher and more violent with the Gaza War. The chronic exposure to trauma and ongoing uncertainty about the future impact physicians and the next generation of healthcare professionals who will care for their traumatized population. Despite the violations of international codes physicians continued to "honor their duties" to their patients and students.